The relationship between social capital and quality of life among rural households in Terengganu, Malaysia - Abdul Hakim, Roslan; Ismail, Russayani; Abdul Razak, Nor Azam (Ontario International Development Agency, 2010)
Social capital has been widely recognised in the recent development literature to have positive consequences on societal well being. However, most studies examine the impact of social capital on some narrow indicators of well being such as income, poverty, education and health. While these indicators do measure and represent the standard of living of the society, and are important development objectives,they focus only on the material aspect of well being.Therefore, it does not really shed light on whether social capital is associated with quality of life which is the subjective aspect of well being.This gives rise to the question on whether social capital also leads to better quality of life. This paper attempts to fill this gap by extending the analysis not only on the impact of social capital on income, but also on quality of life.Empirical evidence on the links between social capital and quality of life is provided by performing regression analysis.The analysis is carried out using primary data obtained from a survey of 2500 rural households in Terengganu, Malaysia. The results show that social capital has a significant impact not only on household income but also on quality of life.These results imply that investment in social capital is crucial to achieve development objectives.